Analysis of Vasoreactivity of Isolated Human Radial Artery - Natasa Stojnic; Ljiljana Gojkovic Bukarica; Miodrag Peric; Marko Bumbasirevic; Aleksandar Lesic; Jasmina Markovic Lipkovski; Helmut Heinle (Elsevier, 2006)
Abstract.: Radial artery (RA) is increasingly used as graft for coronary artery bypass grafting due to its good long-term patency. However, the mechanism of peri- and post-operative spasm is still unclear. Because of that, the aim of our study is to analyze the contractility of RA and to determine whether the presence of functional endothelium alters its contractile properties. Contractions of isolated RA rings were provoked by exogenously applied vasoconstrictors or by electrical field stimulation (EFS, 20 Hz). The order of vasoconstrictors potency based on their EC50 values was as follows: angiotensin II > phenylephrine > 5-hydroxytriptamine. Presence of endothelium increased both EC50 and maximal contraction to phenylephrine and angiotensin II, but inhibited reactivity of RA to 5-hydroxytriptamine. Spontaneous rhythmic contractions (SRC, <4 mHz) and EFS-induced contractions of RA are endothelium-independent and weaker than contractions induced by exogenously applied vasoconstrictors. Our study concludes that RA shows marked sensitivity and reactivity to angiotensin II, phenylephrine, and 5-hydroxy-triptamine. Further investigations are necessary to answer why angiotensin II and phenylepehrine induce stronger contractions in the presence of endothelium. In addition, SRC as well as contractions of neurogenic origin may take part in developing vascular spasm of RA. Keywords:: human radial artery, angiotensin II, phenylephrine, 5-hydroxytriptamine, vasomotion, electrical field stimulation